2021
DOI: 10.1002/1878-0261.12914
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulator BMI1 promotes alveolar rhabdomyosarcoma proliferation and constitutes a novel therapeutic target

Abstract: Rhabdomyosarcoma (RMS) is an aggressive pediatric soft tissue sarcoma. There are two main subtypes of RMS, alveolar rhabdomyosarcoma (ARMS) and embryonal rhabdomyosarcoma. ARMS typically encompasses fusion-positive rhabdomyosarcoma, which expresses either PAX3-FOXO1 or PAX7-FOXO1 fusion proteins. There are no targeted therapies for ARMS; however, recent studies have begun to illustrate the cooperation between epigenetic proteins and the PAX3-FOXO1 fusion, indicating that epigenetic proteins may serve as target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
3
6
0
Order By: Relevance
“… 9 , 11 , 15 , 32 Hence, the therapeutic potential of BMI1 targeting has been widely investigated with many studies describing anti-tumor activity of the inhibitor PTC-209 in different tumors such as DIPG 14 and rhabdomyosarcoma. 38 We show that BMI1 High ;CHD7 Low MB cells are more responsive to PTC treatment while non-neoplastic NSC are not affected by the treatment, as previously reported for other normal/healthy cells, 29 raising the possibility that the treatment would have negligible impact on healthy progenitors in the developing cerebellum.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“… 9 , 11 , 15 , 32 Hence, the therapeutic potential of BMI1 targeting has been widely investigated with many studies describing anti-tumor activity of the inhibitor PTC-209 in different tumors such as DIPG 14 and rhabdomyosarcoma. 38 We show that BMI1 High ;CHD7 Low MB cells are more responsive to PTC treatment while non-neoplastic NSC are not affected by the treatment, as previously reported for other normal/healthy cells, 29 raising the possibility that the treatment would have negligible impact on healthy progenitors in the developing cerebellum.…”
Section: Discussionsupporting
confidence: 76%
“…We show that PTC-209 and PD325901 extend survival of BMI1 High ;CHD7 Low MB xenografts by increasing apoptosis. Induction of apoptosis by PTC-209 or PD325901 administration has been previously reported in other tumors 29 , 38 , 47 , 48 both in vitro and in vivo . Interestingly, a recent study suggested that the new generation BMI1 inhibitor PTC-596 could be more effective in mediating apoptosis in AML when combined with the MEK inhibitor trametinib.…”
Section: Discussionmentioning
confidence: 56%
“…As a matter of fact, RMS cells are thought to derive from mesenchymal progenitors of the skeletal muscle lineage that, despite the expression of the master muscle TFs such as MYOD and MYOG, are unable to differentiate and proliferate indefinitely. In line with this, we and others have demonstrated the involvement of regulators of embryonal tissue differentiation in RMS pathogenesis including the Polycomb proteins EZH2 ( 8 , 9 ) and BMI1 ( 10 ), the Hippo ( 11 13 ), Hedgehog [ ( 14 ); and reviewed in ( 15 )] and NOTCH pathways ( 16 18 ).…”
Section: Introductionsupporting
confidence: 70%
“…A ChIP-seq study in TNBC cells showed that PRC1 complexes (containing CBX8, MEL18/PCGF2, RING1B/RNF2, and PHC2) accumulated at enhancers that were devoid of H3K27me3 and enriched with the transcriptional activator BRD4 62 , suggesting that PRC1 might maintain active expression of some genes. In our previous studies with rhabdomyosarcoma cell lines, PCGF4 inhibition lead to significant downregulation of dozens of genes 41,42 possibly through elevated expression of kinase encoding genes, phosphorylation-mediated inactivation of YAP/TAZ/TEAD, and silencing of YAP/TAZ-target promoters. In another group's study, treatment of glioblastoma multiforme (GBM) cells with PTC596 affected protein levels of transcriptional regulators EZH2, FOXG1, and SOX2.…”
Section: Discussionmentioning
confidence: 91%